Extensive Delayed Brain Atrophy after Resuscitation in a Patient with Multiple System Atrophy - Nisitani, Sazuku; Miyoshi, Hirofumi; Katsuoka, Yoji (Frontiers in Neurology, 2018)
Brain magnetic resonance imaging (MRI) of multiple system atrophy (MSA) shows atrophy in the cerebrum, cerebellum, and brainstem. It is also characterized by specific patterns such as hyperintense lateral putaminal rim. MRI of hypoxic encephalopathy shows atrophy mainly in the gray matter, and laminar necrosis in the cerebral cortex is often observed. Here, we report an MSA patient damaged by hypoxic insult and resuscitated after 18 minute cardiac arrest. The brain of the patient developed severe atrophy within a period of 10 months. Furthermore, brain atrophy was observed in the white and gray matter, which preserved the brain atrophy pattern in MSA. We assume that alpha-synuclein oligomerization is involved in the neural cell death and brain atrophy. It might have caused further neural cell death in the brain damaged by hypoxia. Alpha-synuclein, which is involved in the pathogenesis of MSA, is suggested to be a prion. Misfolded alpha-synuclein may propagate through cell-to-cell transmission and cause wide pathological change, visible as atrophied MR imaging.